Wind power brake pad backboard material and preparation method thereof
By using aluminum-magnesium alloy material containing modified reinforced phase as the back plate of the wind brake pad, the problem of yaw brake disc wear caused by traditional materials is solved, achieving more uniform braking pressure transmission and longer equipment life.
Patent Information
- Application Number
- CN202411865856.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-28
AI Technical Summary
The back plate material of the traditional wind power brake pad causes wear of the yaw brake disc, which in turn affects the braking performance and equipment life.
Materials containing 39% to 69% aluminum, 1% to 5% magnesium, 0~3% zinc, 0~5% copper, 0~2% manganese, 0~2% chromium and 30% to 60% modified reinforced phases are made of materials containing the same charge on the surface, and the wind power brake pad back plate material is prepared.
This material can evenly transmit braking pressure, reduce friction and wear with the yaw brake disc, and extend the service life of the brake disc.
Smart Images

Figure CN119710422A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, and in particular to a wind power brake pad back plate material and a preparation method thereof. Background Art
[0002] The back plates of traditional yaw brake wind turbine brake pads are mostly made of steel materials, which have high specific gravity, strength and hardness, and can better transfer loads to the friction material. However, due to the randomness of wind force and direction during wind power generation, the wear of wind turbine brake pad friction materials cannot be estimated simply based on time, which often leads to the situation where the friction material has been exhausted but the brake pads are not detected and replaced in time. At this time, the back plate will directly contact the yaw brake disc, and the yaw brake disc will quickly wear out due to the friction between the two.
[0003] The yaw brake disc is a large ring with a diameter of about 2 meters. Once its surface is abnormally worn, the thickness of the brake disc will change, which will lead to distortion of the brake pressure transmission and may cause the brake pad to detach, eventually leading to brake failure. In addition, it is extremely difficult to replace the yaw brake disc after the surface is damaged. Usually, when the degree of wear is light, it is necessary to manually grind its surface inside the fan, which is time-consuming and laborious; in the case of severe wear, it is necessary to ensure the thickness of the brake disc by adding insert screws to its surface, which is costly and time-consuming. Therefore, the wear of the yaw brake disc should be avoided as much as possible.
[0004] Research has found that traditional yaw brake discs are mostly made of materials such as 42CrMo, Q345 and QT400, while the brake pad backing plate is usually made of structural steel. The backing plate material is harder than the brake disc material. When the two rub against each other, the brake disc is often worn first. This is also the reason why the yaw brake disc will quickly wear out after the backing plate directly contacts the yaw brake disc. Therefore, there is an urgent need for a material to replace the structural steel material. The backing plate made of this material can not only transfer the braking pressure evenly and completely to the friction material, but also try to avoid wear on the yaw brake disc after contacting it. Summary of the invention
[0005] Based on this, it is necessary to provide a wind turbine brake pad backing plate material, the backing plate made of this material can not only transfer the braking pressure to the friction material evenly and completely, but also minimize the wear on the yaw brake disc after contact with it.
[0006] A wind power brake pad back plate material, the raw materials of which include, by weight percentage, 39% to 69% aluminum, 1% to 5% magnesium, 0 to 3% zinc, 0 to 5% copper, 0 to 2% manganese, 0 to 2% chromium and 30% to 60% modified reinforcing phase; the modified reinforcing phase is soft metal-coated ceramic particles with the same charge on the surface.
[0007] In one embodiment, the ceramic particles are selected from at least one of silicon carbide, zirconium carbide, boron carbide, copper oxide and iron oxide; and the particle size of the ceramic particles is 0.1 to 10 microns.
[0008] In one embodiment, the soft metal is copper.
[0009] In one embodiment, the thickness of the soft metal layer in the soft metal-coated ceramic particles is 100 to 200 microns.
[0010] In one of the embodiments, the aluminum, magnesium, zinc, copper, manganese and chromium in the raw materials are in the form of elemental powder or alloy powder; the elemental powder or alloy powder is a nearly spherical particle, and the particle size of the elemental powder or alloy powder is 20 to 70 microns.
[0011] In one of the embodiments, the wind turbine brake pad back plate material has a tensile strength of ≥300 MPa, an elastic modulus of ≥120 GPa, and a hardness of ≤180 HBW.
[0012] The present application also provides a method for preparing the wind power brake pad back plate material described in any of the above items, and the specific scheme is as follows:
[0013] A method for preparing a wind power brake pad back plate material comprises the following steps:
[0014] providing the raw materials;
[0015] After the raw materials are mixed evenly, they are pressed into a shape to obtain a green body;
[0016] After sintering the green compact, the green compact is cooled to below 50° C. at a rate of above 50° C. / s to obtain the wind power brake pad back plate material.
[0017] In one embodiment, the mixing conditions are: a rotation speed of 30 rpm to 80 rpm, and a time of 1 to 10 hours.
[0018] In one embodiment, when the aluminum, magnesium, zinc, copper, manganese and chromium in the raw materials exist in the form of elemental powders, the pressing pressure is 100MPa~300MPa, and the holding time is 10~20 seconds; when the aluminum, magnesium, zinc, copper, manganese and chromium in the raw materials exist in the form of alloy powders, the pressing temperature is 50℃~250℃, the pressure is 200MPa~400MPa, and the holding time is 20~40 seconds.
[0019] In one of the embodiments, the sintering is carried out in stages: in the first stage, the temperature is increased to 460°C~520°C at a rate of 10°C / min~20°C / min, and kept warm for 1~2 hours; in the second stage, the temperature is increased to 600°C~650°C at a rate of 1°C / min~5°C / min, and kept warm for 10~30 minutes; in the third stage, the furnace is cooled to 520°C~600°C and then taken out of the furnace.
[0020] The above-mentioned wind turbine brake pad back plate material has a tensile strength ≥300MPa, an elastic modulus ≥120GPa, and a hardness ≤180HBW. The back plate made of this material can not only transfer the braking pressure to the friction material evenly and completely, but also minimize its wear after contact with the yaw brake disc. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a comparison chart of wear data of samples prepared using materials of Example 5 and Comparative Examples 1 and 2 on 45# steel;
[0022] Figure 2 This is a comparison chart of the friction coefficient of samples prepared using the materials of Example 5 and Comparative Examples 1 and 2 against 45# steel. DETAILED DESCRIPTION
[0023] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below, and preferred embodiments of the present invention are provided. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0025] The wind power brake pad back plate material of one embodiment comprises raw materials including 39% to 69% by mass of aluminum, 1% to 5% by mass of magnesium, 0% to 3% by mass of zinc, 0% to 5% by mass of copper, 0% to 2% by mass of manganese, 0% to 2% by mass of chromium, and 30% to 60% by mass of a modified reinforcing phase, wherein the modified reinforcing phase is a soft metal-coated ceramic particle with the same charge on the surface.
[0026] In this embodiment, the ceramic particles are selected from at least one of silicon carbide, zirconium carbide, boron carbide, copper oxide and iron oxide, and the particle size of the ceramic particles is 0.1 to 10 micrometers.
[0027] In this embodiment, the soft metal is copper. The thickness of the soft metal layer in the soft metal-coated ceramic particles is 100 to 200 micrometers.
[0028] The thickness of copper in the copper-coated ceramic particles is limited to 100 to 200 microns. On the one hand, during the sintering process, there is a sufficient amount of copper to react with the matrix alloy, penetrate and fuse, and improve the interfacial bonding strength between the modified reinforcing phase and the matrix alloy. On the other hand, during the friction and wear process, a protective film can be formed on the surface of the friction material, effectively reducing the wear of the friction material and stabilizing the friction coefficient.
[0029] In this embodiment, the aluminum, magnesium, copper, manganese and chromium in the above raw materials exist in the form of elemental powder or alloy powder, and the elemental powder or alloy powder is nearly spherical particles, and the particle size of the elemental powder or alloy powder is 20 to 70 microns.
[0030] After the soft metal-coated ceramic particles are treated with surface charges, the problem of particle agglomeration can be effectively solved. And because the surface of the ceramic particles is coated with soft metal, the soft metal will form a protective film on the surface of the friction material. Even if it contacts the yaw brake disc later, it can effectively reduce the wear of the yaw brake disc and stabilize the friction coefficient between them.
[0031] A method for preparing a wind power brake pad back plate material according to an embodiment of the present invention comprises the following steps S110 to S130:
[0032] S110. Provide raw materials.
[0033] The raw material comprises 39% to 69% by mass of aluminum, 1% to 5% by mass of magnesium, 0% to 3% by mass of zinc, 0% to 5% by mass of copper, 0% to 2% by mass of manganese, 0% to 2% by mass of chromium and 30% to 60% by mass of a modified reinforcing phase, wherein the modified reinforcing phase is a soft metal-coated ceramic particle with the same charge on the surface.
[0034] In this embodiment, the preparation method of the modified reinforcing phase is shown in S1101 to S1102:
[0035] S1101, providing ceramic particles;
[0036] The ceramic particles are selected from at least one of silicon carbide, zirconium carbide, boron carbide, copper oxide and iron oxide.
[0037] Furthermore, the particle size of the ceramic particles is 0.1 to 10 microns.
[0038] S1102, depositing a soft metal layer on the surface of the ceramic particles by plasma-assisted chemical vapor deposition to obtain soft metal-coated ceramic particles with the same charge on the surface.
[0039] Among them, the soft metal is copper.
[0040] Furthermore, the thickness of the soft metal layer is 100 to 200 microns.
[0041] It should be noted that the thickness of the soft metal layer cannot be too thick, otherwise the reinforcing effect of the ceramic particles cannot be effectively exerted, and the thickness of the soft metal layer cannot be too thin, otherwise it cannot form an effective protective layer on the surface of the friction material.
[0042] Specifically, a soft metal precursor (such as an organic metal compound of copper) is heated to decompose it by chemical vapor deposition (CVD) to produce soft metal, which is then deposited on the surface of ceramic particles to form a soft metal layer. During the deposition process, the surface of the ceramic particles is treated with plasma, and charged particles directly bombard the surface of the ceramic particles and the surface of the soft metal, causing ionization or electronic excitation of the soft metal surface, thereby obtaining soft metal-coated ceramic particles with the same charge on the surface.
[0043] It can be understood that the soft metal-coated ceramic particles with the same surface charge are not limited to being prepared by the above method, and only one of the preparation methods is given here.
[0044] In this embodiment, the aluminum, magnesium, zinc, copper, manganese and chromium in the above raw materials are in the form of elemental powder or alloy powder. Further, the elemental powder or alloy powder is a nearly spherical particle; the particle size of the elemental powder or alloy powder is 20 to 70 microns.
[0045] S120, after the above raw materials are evenly mixed, they are pressed into a shape to obtain a green body.
[0046] It should be noted that there is no particular limitation on the mixing conditions as long as the above raw materials can be mixed evenly. However, considering the need to maintain the soft metal layer of the modified reinforcement phase as much as possible, in this embodiment, the mixing conditions are: a rotation speed of 30 rpm to 80 rpm and a time of 1 to 10 hours.
[0047] It should be noted that the pressing conditions need to be adjusted according to the form of the raw materials. Specifically, when aluminum, magnesium, zinc, copper, manganese and chromium exist in the form of single powder in the raw materials, the pressing pressure is 100MPa~300MPa, and the holding time is 10~20 seconds. When aluminum, magnesium, zinc, copper, manganese and chromium exist in the form of alloy powder in the raw materials, the pressing pressure is 200MPa~400MPa, and the holding time is 20~40 seconds.
[0048] S130, cooling the green compact to below 50°C at a rate of above 50°C / s after sintering, to obtain a wind power brake pad back plate material.
[0049] It can be understood that cooling the green body to below 50°C at a rate of more than 50°C / s after sintering can ensure uniform grain size inside the material, reduce or even avoid precipitation of the second phase or precipitates during the cooling process, and effectively improve the strength of the material.
[0050] In this embodiment, sintering is carried out in stages: in the first stage, the temperature is increased to 460°C~520°C at a rate of 10°C / min~20°C / min, and kept warm for 1~2 hours; in the second stage, the temperature is increased to 600°C~650°C at a rate of 1°C / min~5°C / min, and kept warm for 10~30 minutes; in the third stage, the steel is cooled to 520°C~600°C with the furnace and then taken out of the furnace.
[0051] The staged sintering method can effectively ensure the thickness and stability of the soft metal layer during the sintering process, obtain higher material density and mechanical properties, and the sintered material can be used without shaping.
[0052] The wind turbine brake pad back plate material prepared by the above method has a tensile strength of ≥300MPa, an elastic modulus of ≥120GPa, and a hardness of ≤180HBW. The back plate prepared by the material can not only transfer the braking pressure to the friction material evenly and completely, but also avoid wear on the yaw brake disc after contact with it.
[0053] The following are specific embodiments.
[0054] Example 1
[0055] The wind power brake pad material is prepared by the method of steps S110 to S130. The material includes 39% aluminum, 1% magnesium and 60% modified reinforcement phase. The modified reinforcement phase is copper-coated zirconium carbide particles with the same charge on the surface.
[0056] Example 2
[0057] The wind power brake pad material is prepared by the method of steps S110 to S130. The material includes 39% aluminum, 1% magnesium and 60% modified reinforcement phase. The modified reinforcement phase is copper-coated silicon carbide particles with the same charge on the surface.
[0058] Example 3
[0059] The wind power brake pad material is prepared by the method of steps S110 to S130. The material includes 69% aluminum, 1% magnesium and 30% modified reinforcing phase. The modified reinforcing phase is copper-coated silicon carbide particles with the same charge on the surface.
[0060] Example 4
[0061] A wind turbine brake pad material is prepared by the method of steps S110 to S130. The material includes 45% aluminum, 5% magnesium, 3% zinc, 5% copper, 2% manganese, 2% chromium and 38% modified reinforcing phase, wherein the modified reinforcing phase is copper-coated boron carbide particles with the same charge on the surface.
[0062] Example 5
[0063] A wind turbine brake pad material is prepared by the method of steps S110 to S130, wherein the material includes 50% aluminum, 3% magnesium, 2% zinc, 2% copper, 1% manganese and 42% modified reinforcing phase, wherein the modified reinforcing phase is copper-coated copper oxide particles with the same charge on the surface.
[0064] Example 6
[0065] The wind turbine brake pad material is prepared by the method of steps S110 to S130. The material includes 55% aluminum, 2% magnesium, 1% zinc, 2% manganese, 1% chromium and 39% modified reinforcing phase, wherein the modified reinforcing phase is copper-coated iron oxide particles with the same charge on the surface.
[0066] Comparative Example 1
[0067] Comparative Example 1 is substantially the same as Example 5, except that the modified reinforcing phase in Comparative Example 1 is silicon carbide particles.
[0068] Comparative Example 2
[0069] Comparative Example 2 is substantially the same as Example 5, except that the thickness of the modified reinforcing phase copper coating in Comparative Example 2 is 50 μm.
[0070] The materials of Example 5, Comparative Example 1 and Comparative Example 2 were used to prepare friction and wear test samples, respectively. The friction coefficient change curves of 45# steel were as follows: Figure 1 and Figure 2 The results are shown in Tables 1 to 3 respectively.
[0071] Table 1
[0072]
[0073] Table 2
[0074]
[0075] Table 3
[0076]
[0077] From Tables 1 to 3 and Figure 1 , 2It can be seen that although comparative example 2 has the highest friction coefficient and the lowest wear rate, its friction coefficient fluctuates greatly, which is not conducive to accurate braking. While example 5 has the lowest wear rate, its friction coefficient curve is stable and easy to accurately control, and is more suitable for braking.
[0078] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A wind power brake pad back plate material, characterized in that: The raw materials include, by mass percentage, 39% to 69% aluminum, 1% to 5% magnesium, 0% to 3% zinc, 0% to 5% copper, 0% to 2% manganese, 0% to 2% chromium and 30% to 60% modified reinforcing phase; the modified reinforcing phase is soft metal-coated ceramic particles with the same charge on the surface.
2. The wind power brake pad back plate material according to claim 1, characterized in that: The ceramic particles are selected from at least one of silicon carbide, zirconium carbide, boron carbide, copper oxide and iron oxide; and the particle size of the ceramic particles is 0.1 to 10 microns.
3. The wind power brake pad back plate material according to claim 1, characterized in that: The soft metal is copper.
4. The wind power brake pad back plate material according to claim 3, characterized in that: The thickness of the soft metal layer in the soft metal-coated ceramic particles is 100 to 200 microns.
5. The method for preparing the wind power brake pad back plate material according to claim 1, characterized in that: The aluminum, magnesium, zinc, copper, manganese and chromium in the raw materials exist in the form of elemental powder or alloy powder; the elemental powder or alloy powder is nearly spherical particles, and the particle size of the elemental powder or alloy powder is 20 to 70 microns.
6. The wind power brake pad backing material according to any one of claims 1 to 5, characterized in that: The tensile strength of the wind power brake pad back plate material is ≥300MPa, the elastic modulus is ≥120GPa, and the hardness is ≤180HBW.
7. A method for preparing a wind power brake pad back plate material according to any one of claims 1 to 6, characterized in that: The following steps are involved: providing the raw materials; After the raw materials are mixed evenly, they are pressed into a shape to obtain a green body; After sintering the green compact, the green compact is cooled to below 50° C. at a rate of above 50° C. / s to obtain the wind power brake pad back plate material.
8. The method for preparing the wind power brake pad back plate material according to claim 7, characterized in that: The mixing conditions are: a rotation speed of 30 rpm to 80 rpm, and a time of 1 to 10 hours.
9. The method for preparing the wind power brake pad back plate material according to claim 7, characterized in that: When the aluminum, magnesium, zinc, copper, manganese and chromium in the raw materials exist in the form of elemental powders, the pressing pressure is 100MPa-300MPa, and the holding time is 10-20 seconds; when the aluminum, magnesium, zinc, copper, manganese and chromium in the raw materials exist in the form of alloy powders, the pressing temperature is 50°C-250°C, the pressure is 200MPa-400MPa, and the holding time is 20-40 seconds.
10. The method for preparing the wind power brake pad back plate material according to claim 7, characterized in that: The sintering is carried out in stages: in the first stage, the temperature is increased to 460°C-520°C at a rate of 10°C / min-20°C / min, and kept warm for 1-2 hours; in the second stage, the temperature is increased to 600°C-650°C at a rate of 1°C / min-5°C / min, and kept warm for 10-30 minutes; in the third stage, the sintered steel is cooled to 520°C-600°C with the furnace and then taken out of the furnace.